Cytomegalovirus in Pregnant Woman - Abdul Amir, Dr. Venus Hassan (Clinical Medicine And Health Research Journal, 2024)
Fourty patients were diagnosed with Cytomegalovirus in pregnant with fever, weariness, and lymphadenitis. ELISA was recycled to check CMV IgG antibodies. A entire of 40 patients sera infested by means of lymphadenitis plus 40 regulator sera joined hip this learning be present calculated in place of IL-17 and IL-1β levels in their blood. The results point to significant transformation amongst patients and control for IL-17, while no difference between them at IL-1β.